Relapse after Prolonged Remission in Philadelphia-Like Acute Lymphoblastic Leukemia. (21st January 2019) - Shah, Gaurav; Mikhail, Fady M.; Carroll, Andrew J.; Kutny, Matthew; Papadantonakis, Nikolaos
Abstract : We describe a case of late relapse of Philadelphia-like acute lymphoblastic leukemia. The patient relapsed several years from diagnosis and responded to second salvage treatment. The case highlights the open questions regarding management of Philadelphia-like acute lymphoblastic leukemia.